Evaluasi Kerusakan Jalan Merpati Sakti Dengan Metode Pavement Condition Index (PCI) - Elianora; Rurianti, Dwi Visti; Misriani, Merley; Marpaung, Horas Saut; Djuniati, Sri; Sitepu, Epa Lukesih (Teknik Sipil Universitas Riau, 2024)
Road damage is a condition where the quality of the road pavement decreases so that it can disrupt the comfort and safety of road users. On the Merpati Sakti road there is a lot of damage which can pose a risk of accidents. The aim of this research is to determine the types of damage and determine the index value of the flexible pavement condition on Merpati Sakti road. This research method uses the Pavement Condition Index (PCI) method. The data required includes the type of road damage, road dimensions, damage dimensions. The results of identifying the types of road damage found along the research location bleeding, potholes, depression, weathering/raveling, block crack, alligator cracks, diagonal cracks, transverse cracks, edge cracking and patching. The average Pavement Condition Index (PCI) value on Merpati Sakti road is 21.5. From the results of this research it can be concluded that the damage on Merpati Sakti road using the PCI (Pavement Condition Index) method is very poor. The recommendations from this research require serious treatment from the government to immediately carry out repairs so that the damage does not become worse.